САЛАФИЙ ЖАНА ФАЛСАФИЙ УСУЛ -ТЕОРИЯЛЫК ЖАНА ПРАКТИКАЛЫК КАРАМА-КАРШЫЛЫКТАР БОЮНЧА БОРБОРДУК АЗИЯ АЛКАГЫНДА - Уянык, Мевлүт; Ажимаматов, Зайлабидин (Scientific Journal of Faculty of Theology, 2015)
Since the first prophets the basic principles (Tavhid- Nubuvvat - Mead) at different times, in different direction and in different languages were spread by prophets (Nabi/Rasul) The Prophet Muhammed a single prophet and there is no prophet after him, that‘s why we should observe the main principles and adhere the way of life of sahabas and tabuins. On this basis, today arose two main methods (Salafii and Falsafii) for the solution of the policies, economic and social issues of Muslims. The aim of research based on the methods of evidence, discuss and explain for revealing of quality and justice of those two main methods.